2012
DOI: 10.1111/dth.12006
|View full text |Cite
|
Sign up to set email alerts
|

Vitiligo road map

Abstract: Vitiligo is a depigmenting disorder stemming from melanocyte loss or dysfunction. It has a complex, multifaceted etiology. We constructed a "vitiligo road map," consisting of basic science, clinical, and treatment components, in order to better portray our current understanding of vitiligo pathogenesis and reflect upon novel biomarkers and therapeutic targets for future research. The melanocyte map elaborates on the molecular processes and intracellular signaling pathways initiated by various external autocrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 145 publications
0
24
0
Order By: Relevance
“…Although it is not physically harmful, vitiligo is often psychologically devastating due to the depigmented macules on the skin that result from the selective loss of functional epidermal melanocytes [2418]. Amelanotic melanocytes in the outer root sheath of hair follicles have been shown to migrate towards the achromic epidermis during the process of repigmentation and gradually restore the normal functions of melanin synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is not physically harmful, vitiligo is often psychologically devastating due to the depigmented macules on the skin that result from the selective loss of functional epidermal melanocytes [2418]. Amelanotic melanocytes in the outer root sheath of hair follicles have been shown to migrate towards the achromic epidermis during the process of repigmentation and gradually restore the normal functions of melanin synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The expression levels of tyrosinase and its related proteins (tyrosinase-related protein 1 and tyrosinase-related protein 2) are mainly regulated by microphthalmia transcription factor (MITF), which is an important regulator of melanocyte differentiation, proliferation and survival and is highly coupled with melanogenesis [1827]. Any therapy for vitiligo must promote not only the repopulation of melanocytes but also melanogenesis and melanocyte migration.…”
Section: Discussionmentioning
confidence: 99%
“…Keratinocytes supply essential growth factors for melanocyte growth . Keratinocyte‐derived factors like endothelin‐1, stem cell factor ( SCF ), basic fibroblast growth factor ( bFGF ) and nerve growth factor, etc., help in melanogenesis . A mice study has shown that SCF and bFGF should be supplied in the culture medium for the in‐vitro proliferation of melanocyte stem cells .…”
Section: Cellular Transplantation Methodsmentioning
confidence: 99%
“…It occurs clinically by the appearance of well-circumscribed, asymptomatic, white macules following the loss of functional melanocytes in the epidermis (1). The prevalence rate of vitiligo ranges from 0.06% to 2.28% in the population (2).…”
Section: Introductionmentioning
confidence: 99%
“…The main etiopathogenesis of vitiligo is multifactorial. According to various pathophysiological theories, it may be associated with autoimmunity, neurogenic dysregulation, autocytotoxicity, biochemical dysregulation, oxidative stress, and weak melanocyte viability (1,(3)(4)(5)(6). Several potentially environmental factors such as infectious agents appear to be related with vitiligo (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%